Educación para Todos de Llach, ]uan ]osé; Montoya, Silvia; y Roldán, Flavia Buenos Aires, 1999, IERAL, 528 págs. - Alles, Santiago Manuel (2001)
Fil: Alles, Santiago M. Pontificia Universidad Católica Argentina; Argentina